Review: Extraction of Temulawak Rhizome (Curcuma xanthorrhiza Roxb.) and Activity As Antibacterial - Yasacaxena, Lidvina Niken; Defi, Matea Nirmala; Kandari, Vicha Putri; Weru, Putri Teresa Rery; Papilaya, Feranita Elsa; Oktafera, Melania; Setyaningsih, Dewi (Tropical Biopharmaca Research Center, IPB University, 2023)
Temulawak (Curcuma xanthorrhiza) is one of Indonesia’s native plants belonging to Zingiberaceae family. The plant has been extensively used for treatment of various diseases such as inflammation and digestive tract swelling, gallstones, liver, dyspepsia, and antispasmodic. The rhizome becomes the plant’s part that is used the most. The rhizome contains a compound that could work as an antibacterial. An extract of the rhizome may be obtained through extraction process, some extractions that would be used in this research review is soxhletation, maceration, and ultrasound assisted extraction (UAE). As various extraction methods both involving simple and complex ones were found, it was shown that the result of extract content are therefore varied, which was also affecting the level of resulted antibacterial effectiveness. This article was carried out to analyze the most suitable extraction method of Curcuma’s rhizome that results the highest effectiveness of antibacterial activity. The method used in this article review was a literature review on the literatures published during the period of 2012 to 2022. The highest average yield was shown on maceration method which respectively was followed by soxhletation whereas the lowest yield was resulted by UAE method